(untitled) (Raparin Journal of Humanities (RJH), 2025)
This work is entitled (Character Personality Typology in (Lasar Baran Danusm - I Write on the Rain) Novel from the perspective of Carl Gustav Jung( Narrative literature has occupied a wide space in world literature today and a significant number of novels and stories are published annually in the world. Critics, theorists and researchers study these works in an academic and scientific manner. The result of these studies is the emergence of an important scientific discipline known as “narratology”. Based on scientific methods and critical theories, narratology identifies and directs research types in narrative literature. In this discipline, narratology benefits from the results of the humanity sciences such as philosophy, psychology, sociology, mythology, etc. Narrative in novels, stories and other forms of narrative literature is presented on the basis of language and language expressing ways through different arts and techniques. “Monologue” is one of the most important forms of language expressing in narrative literature that manifests the psychological state, worldview and way of thinking of the character, and the psychological state gets the main share of character introduction in this technique. In this research, based on the Carl Gustav’s Personality Typology Theory, which is known as Introversion and Extroversion, attempt is made to present (Character Personality Typology) in (Lasar Baran Danusm) novel.